Effective Troubleshooting of EZ-Blocker™ Endobronchial Blocker Insertion in Minimally Invasive CABG Surgery: A Case Series - Arupratan Maiti; Sreya Moitra; Amrita Guha (Journal of Clinical and Diagnostic Research)
EZ-Blocker™ is a specially designed semi-rigid Y-shaped Bronchial Blocker (BB) containing two inflatable cuffs. The difficulties and challenges encountered while inserting the Rusch EZ-Blocker™ (Teleflex Life Sciences Ltd., Athlone, Ireland) for isolating the left lung in Minimally Invasive Coronary Artery Bypass Graft (MICS CABG) surgery are numerous and varied. The present case series describes 28 different patients (out of 102 patients with attempted EZ-Blocker™) who faced various difficulties and technical problems while introducing the EZ-Blocker™ and how troubleshooting was performed in those cases with different manoeuvres. The difficulties in inserting the EZ-Blocker™ were due to a variety of reasons such as inadequate space between the carina and bronchus, a prominent right main bronchus at an acute angle compared to the obtuse angle of the left main bronchus, a compressed left main bronchus, deviation of the airway and a deep posterior bronchus. The manoeuvres used to overcome these challenges included controlled pulling of the endotracheal tube upwards, rotation of the head to the right-side with or without direct tracheal manual compression to the right-side, manual widening of the distal Y end of the EZ-Blocker™ and extension of the head in selected cases. Out of 102 attempted cases of EZ-Blocker™, difficulty (insertion time >90 seconds) was noted in 28 cases, which were managed with the different clinical manoeuvres mentioned above. However, in four other cases, the EZ-Blocker™ could not be introduced and the attempts failed. Although the EZ-Blocker™ is a safe and easy alternative to the Double Lumen Tube (DLT), it has not been widely used in India to date. The proposed manoeuvres will surely help clinicians use it more efficiently in cases where they encounter difficulty during insertion.